The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/09637214221121295
|View full text |Cite
|
Sign up to set email alerts
|

How Do LGBTQ+ Parents Raise Well-Adjusted, Resilient, and Thriving Children?

Abstract: Lesbian, gay, bisexual, transgender, and queer (LGBTQ+) parents raise well-adjusted children. How do they accomplish this feat despite stigma and discrimination? Psychological scholarship (often based in the United States and other Westernized countries) has typically used atheoretical, deficit models based on biased assumptions to compare the outcomes of children of LGBTQ+ parents and children of cisgender heterosexual parents. However, research on processes and socialization within LGBTQ+-parent families sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 31 publications
3
39
0
Order By: Relevance
“…The decision to keep this portion of the model the same as Meyer's (2003) original minority stress model was influenced by findings from studies we reviewed that show that stressors still have a direct effect on the mental health outcomes for queer individuals and families (e.g., Bockting et al, 2013; Fulginiti et al, 2020; Green et al, 2022) and that coping and social support impact the strength of this effect (e.g., Mereish et al, 2022; Meyer, 2015; Wong et al, 2014). We urge the use of the TIMS model to support the efforts of scholars who have shifted the focus of LGBTQ+ research from a deficit approach to a strengths‐based one by highlighting queer joy (Travers et al, 2022), resistance (e.g., Robinson & Schmitz, 2021), and thriving (Farr et al, 2022). This paradigm shift helps to highlight the positive experiences that LGBTQ+ families encounter in their day‐to‐day lives.…”
Section: Comparing and Contrasting Mst And Tims Modelsmentioning
confidence: 99%
“…The decision to keep this portion of the model the same as Meyer's (2003) original minority stress model was influenced by findings from studies we reviewed that show that stressors still have a direct effect on the mental health outcomes for queer individuals and families (e.g., Bockting et al, 2013; Fulginiti et al, 2020; Green et al, 2022) and that coping and social support impact the strength of this effect (e.g., Mereish et al, 2022; Meyer, 2015; Wong et al, 2014). We urge the use of the TIMS model to support the efforts of scholars who have shifted the focus of LGBTQ+ research from a deficit approach to a strengths‐based one by highlighting queer joy (Travers et al, 2022), resistance (e.g., Robinson & Schmitz, 2021), and thriving (Farr et al, 2022). This paradigm shift helps to highlight the positive experiences that LGBTQ+ families encounter in their day‐to‐day lives.…”
Section: Comparing and Contrasting Mst And Tims Modelsmentioning
confidence: 99%
“…Overall, research has shown that lesbian and gay parents experienced heightened levels of stress and anxiety during the pandemic, also related to concerns about their children’s well-being and the potential for discrimination or prejudice (Goldberg et al, 2021; Salerno et al, 2020). Further examination of parental burnout in parents with minoritized sexual identities is needed, given that they face partially different stressors (e.g., they tend to experience more stigmatization and less social support; Leal et al, 2021) but also benefit from partially different resources (e.g., they typically demonstrate a more egalitarian division of unpaid household and childcare labor; Carone & Lingiardi, 2022; Farr et al, 2022), relative to heterosexual parents. Therefore, the present study examined some factors associated with parental burnout during the COVID-19 pandemic in lesbian and gay parents with school-age children born through assisted reproduction.…”
Section: Coparenting and Parental Burnout Prior To And During The Cov...mentioning
confidence: 99%
“…Instead, we should be “setting our own agendas” in our research, and resisting the urge to engage with offensive and anti‐LGBTQ+ research and theorizing (Clarke, 2000, p. 157). Setting our own agendas may lead us to explore long‐understudied and difficult topics within LGBTQ+ parent families—as well as, or perhaps in concert with, choosing to focus on the many strengths and resilience of LGBTQ+ parent families (e.g., Farr et al, 2022; Gartrell et al, 2019).…”
Section: Professionalmentioning
confidence: 99%